How do you use the limit definition of the derivative to find the derivative of #f(x)=sqrt(x-4)#?
Please see the explanation for details on how you do the requested process.
The limit definition is:
Given:
Substituting into the definition:
This will square the square roots in the numerator and, eventually, leave nothing but h:
Squaring the square roots makes them disappear:
Distribute the - through the ()s in the numerator:
The numerator simplifies to become only h:
Combine the terms in the denominator:
By signing up, you agree to our Terms of Service and Privacy Policy
To use the limit definition of the derivative to find the derivative of (f(x) = \sqrt{x - 4}), we start by applying the definition:
[ f'(x) = \lim_{{h \to 0}} \frac{{f(x + h) - f(x)}}{h} ]
Substitute (f(x) = \sqrt{x - 4}) into the formula:
[ f'(x) = \lim_{{h \to 0}} \frac{{\sqrt{x + h - 4} - \sqrt{x - 4}}{h}} ]
To simplify the expression, we multiply the numerator and denominator by the conjugate of the numerator:
[ f'(x) = \lim_{{h \to 0}} \frac{{(\sqrt{x + h - 4} - \sqrt{x - 4})(\sqrt{x + h - 4} + \sqrt{x - 4})}}{h(\sqrt{x + h - 4} + \sqrt{x - 4})} ]
After expanding and simplifying, we get:
[ f'(x) = \lim_{{h \to 0}} \frac{{(x + h - 4) - (x - 4)}}{h(\sqrt{x + h - 4} + \sqrt{x - 4})} ]
[ f'(x) = \lim_{{h \to 0}} \frac{{x + h - 4 - x + 4}}{h(\sqrt{x + h - 4} + \sqrt{x - 4})} ]
[ f'(x) = \lim_{{h \to 0}} \frac{h}{h(\sqrt{x + h - 4} + \sqrt{x - 4})} ]
[ f'(x) = \lim_{{h \to 0}} \frac{1}{\sqrt{x + h - 4} + \sqrt{x - 4}} ]
Now, we let (h) approach 0:
[ f'(x) = \frac{1}{\sqrt{x - 4} + \sqrt{x - 4}} ]
[ f'(x) = \frac{1}{2\sqrt{x - 4}} ]
So, the derivative of (f(x) = \sqrt{x - 4}) is (f'(x) = \frac{1}{2\sqrt{x - 4}}).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- What is the equation of the normal line of #f(x)=x^2/(1+4x)# at #x=-1#?
- What is the equation of the tangent line of #f(x) =(x^2)/(x-4)# at #x=5#?
- How do you use the limit definition of the derivative to find the derivative of #f(x)=3x^2+3x+3#?
- What is the equation of the normal line of #f(x)= -2x^3-10x # at #x=2 #?
- What is the equation of the line tangent to #f(x)=(2x^2 - 1) / x# at #x=1#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7